3-Dimensional stable polyelectrolyte hollow capsules: preparation and spontaneous encapsulation. Issue 3 (5th January 2017) - Chen, Y. D.; Xu, J. J.; Wang, Y.; Chen, H.; Luo, Q. J.; Li, X. D.; Zhu, W. P.
Abstract : By alternatively depositing poly(styrene)- co -poly(acrylic acid) and poly(allylamine hydrochloride) on poly(styrene sulfonate sodium) hybrid CaCO3 microparticles, a series of size-controlled 3-dimensional stable capsules were obtained after the removal of hybrid templates. Abstract : In this study, by alternatively depositing a poly(styrene)- co -poly(acrylic acid)/poly(allylamine hydrochloride) multilayer on the poly(styrene sulfonate sodium) hybrid CaCO3 spherical templates, a series of size-controlled and low-dispersed polyelectrolyte capsules were obtained after the removal of hybrid templates. These polyelectrolyte capsules can retain their 3-dimensional spheric shape after being dried at room temperature. Through investigating the structure and key factors for the formation of novel capsules, formation mechanism of the 3-dimensional stable capsule wall was discussed. Further investigation showed that the dry capsules could spontaneously entrap water-soluble positively charged substances from the bulk solution into the capsule interior, just like the wet capsules.